Ownership Structure and Board of Directors: Predicting the Performance of the Consumer Goods Industry in Indonesia - Alriansyah Manurung, Muhammad Rizqi; Juli Riyanto Tri Wijaya (Universitas Muhammadiyah Purwokerto, 2025)
The global economy is rapidly advancing, driven by the growth of resources in both developed and emerging economies, such as Indonesia. Companies are increasingly focused on meeting market and external demands dynamically, aiming to optimize shareholder success and enhance the value of their institutions. This study aims to examine whether family ownership positively impacts company performance, institutional ownership positively influences company performance, blockholder ownership has a positive effect on company performance, and the board of directors contributes positively to company performance in Indonesia's consumer goods industry. The findings of this study suggest that family ownership does not significantly impact company performance, blockholder ownership does influence company performance, and the direction of the board of directors plays a role in shaping company performance within the consumer goods sector in Indonesia.